Strategic Management In Imporoving The Quality Of Islamic Education At Mataram State Islamic University - Ais Saputra; Sadya Santosa; Sadam Husain; Erik Junaidi; Muhammad Zaenal Lael (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the implementation of strategic management in improving the quality of Islamic education at the State Islamic University (UIN) Mataram using a descriptive qualitative method with a case study approach through semi-structured interviews, observations, and documentation studies analyzed with the interactive model of Miles and Huberman. The results of the study indicate that UIN Mataram implements strategic management through three main stages, namely strategy formulation, strategy implementation, and strategy evaluation which are realized through institutional transformation from IAIN to UIN, curriculum development based on the integration of religious and general sciences, improving the quality of human resources through continuous training, developing educational infrastructure and facilities, and strengthening the internal quality assurance system with a strategy of scientific integration as a characteristic to create graduates who excel academically and have a strong spirituality. Supporting factors for the implementation of strategic management include visionary leadership, collaborative organizational culture, and regulatory support from the Ministry of Religious Affairs, while the challenges faced include limited human resources, resistance to change, lack of infrastructure, and competition with other universities. This study concludes that strategic management plays a central role in improving the quality of Islamic education at UIN Mataram through an adaptive approach, responsive to the dynamics of changing times, and maintaining Islamic values as the main foundation.